Keanekaragaman Jenis Capung (Odonata) dan Hubungannya dengan Vegetasi di Sungai Winongo, Bantul, Yogyakarta - Shaim Basyari; Nadilla Audrey Aurellie Wibowo; Zahira Nabila Suseno (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2025)
Research on the diversity of dragonflies in the Winongo River, Bantul Regency, Yogyakarta is very important to be carried out as an effort to obtain basic data for further research. The purpose of this study was to determine the types of dragonflies (odonata) and the effect of vegetation on the diversity of dragonflies (odonata) as bioindicators in the Winongo River, Bantul, Yogyakarta. The purposive technique was used to determine the data/sampling stations based on differences in vegetation around the Winongo River. The first location is on the banks of the river with vegetation dominated by bamboo clumps. The second location is on the edge of the river with heterogeneous vegetation. The third location on the banks of the river is a rice field. The fourth location is on the banks of the Winongo River in the form of a settlement. The study was conducted for 5 months, namely April to August 2024. The time for collecting research data was carried out in the morning at 08.00-10.00 and in the afternoon at 16.00-18.00 when the dragonflies were active. The observation data were then analyzed using qualitative descriptive techniques. The results of the study showed that there were 23 species of dragonflies in the Winongo River, Bantul Regency, Yogyakarta, consisting of 20 genera and 6 families from 2929 individuals that were successfully recorded. The diversity of dragonflies in the Winongo River, Bantul Regency, Yogyakarta is included in the good category with a Diversity Index of 1.93. The highest Diversity Index is found in the rice field habitat type, namely 1.94 with the largest number of dragonfly species (17 species). In habitat types with low light intensity such as bamboo groves and heterogeneous habitat types, it is dominated by Libellago lineata, reaching 70.41% and 41.40% respectively. In more open habitats with high light intensity such as rice fields and settlements, it is dominated by Brachythemis contaminata, reaching 32.51% and 63.31% respectively.